Drivers of multi-destination tourism in APEC (2008-2023) - Chanakan Thongma; Chia-Lin Chang (Annals of Tourism Research Empirical Insights, 2025)
This study examines the economic and policy factors shaping multi-destination tourism flows in the Asia-Pacific Economic Cooperation region, focusing on Japan, Taiwan, and Thailand from 2008 to 2023. Using gravity model and vector autoregression analysis, it identifies GDP, exchange rates, visa policies, government efficiency, and travel distance as key determinants. Results show Japan attracts high-income tourists, Taiwan acts as a transit hub, and Thailand appeals to budget-conscious travelers. The analysis highlights both competitive and complementary dynamics, underscoring the need for regional tourism coordination. The proposed "Sustainable Asia Tourism Trail" supports the United Nations SDGs by encouraging environmentally friendly travel and cross-border cooperation. Policy recommendations include streamlining visas, investing in infrastructure, and implementing coordinated strategies to strengthen regional competitiveness and sustainability.
Keywords: 330; APEC; Gravity model; Multi-destination tourism; Regional tourism dynamics; Sustainable tourism policies